Wild kratts. Creepy creatures! [videorecording (DVD)] (PBS Kids, 2019)
"The Wild Kratts aren't sure what to do for Halloween. Should they go trick-or-treating, or just enjoy a Halloween party? The Kratt Brothers decide that the best thing to do is to discover some new 'creepy, cool' creatures. But when they set off to find these new animal friends, Martin and Chris discover that Zach and the other villains have come up with a plan to ruin Halloween. Can the Wild Kratts defeat the villains and still get to celebrate Halloween?"--Container